Unlocking the Role of Exercise on CD4+ T Cell Plasticity - Goldsmith, Chloé D.; Donovan, Thomasina; Vlahovich, Nicole; Pyne, David B. (Frontiers in Immunology, 2021)
A hallmark of T cell ageing is a loss of effector plasticity. Exercise delays T cell ageing, yet the mechanisms driving the effects of exercise on T cell biology are not well elucidated. T cell plasticity is closely linked with metabolism, and consequently sensitive to metabolic changes induced by exercise. Mitochondrial function is essential for providing the intermediate metabolites necessary to generate and modify epigenetic marks in the nucleus, thus metabolic activity and epigenetic mechanisms are intertwined. In this perspective we propose a role for exercise in CD4+ T cell plasticity, exploring links between exercise, metabolism and epigenetic reprogramming.